2018
DOI: 10.14715/cmb/2018.64.3.6
|View full text |Cite
|
Sign up to set email alerts
|

The determination of the effect of some 1,3,4 thiadiazole derivatives on biochemical content (Fatty Acids, Sterols, Lipophilic Vitamins) in rat liver

Abstract: Thiadiazole derivatives and its metal compounds have antibacterial, antifungal, antitumoral, antiproliferative and antioxidant properties. In the study, the effects caused by thiadiazole ligand and its metal complexes upon the fatty acids and lipophilic vitamins in livers of rats were examined. The fatty acids in liver were specified by GC while the lipophilic vitamins were specified by HPLC. It was observed that the amounts of oleic acids (18:1, n-9) and monounsaturated fatty acids (MUFA) notably increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In a study brought about by Parlak et al (2018) investigated effects of hydroxyurea derivative 1,3,4thiadiazoles on fatty acids and lipophilic vitamins in rats liver. In this study, it was indicated that, while amounts of oleic acid (18: 1, n-9) and monounsaturated fatty acids (MUFA) increased significantly in Mn complex group compared to the control group, arachidonic acid amount (20: 4, n-6) in ligand group increased significantly, in addition, α-tocopherol amounts and K 2 and D 3 vitamins increased significantly in all groups compared to the control group, increases of αtocopherol amounts in both Mn and Cr complex groups were found closer to each other compared to the control group, and retinol amount in Mn complex group was lower compared to other groups.…”
Section: J Cell Neurosci Oxidmentioning
confidence: 99%
“…In a study brought about by Parlak et al (2018) investigated effects of hydroxyurea derivative 1,3,4thiadiazoles on fatty acids and lipophilic vitamins in rats liver. In this study, it was indicated that, while amounts of oleic acid (18: 1, n-9) and monounsaturated fatty acids (MUFA) increased significantly in Mn complex group compared to the control group, arachidonic acid amount (20: 4, n-6) in ligand group increased significantly, in addition, α-tocopherol amounts and K 2 and D 3 vitamins increased significantly in all groups compared to the control group, increases of αtocopherol amounts in both Mn and Cr complex groups were found closer to each other compared to the control group, and retinol amount in Mn complex group was lower compared to other groups.…”
Section: J Cell Neurosci Oxidmentioning
confidence: 99%
“…Thiadiazole derivatives and its metal compounds have antibacterial, antifungal, antitumoral, antiproliferative and antioxidant properties. The effects caused by thiadiazole ligand and its metal complexes upon the fatty acids and lipophilic vitamins in livers of rats were examined by Parlak et al [18]. Many methods were employed for the determination of 1,3,4-thiadiazoles.…”
Section: Introductionmentioning
confidence: 99%